2017
DOI: 10.1002/smll.201701232
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer Tungsten Disulfide (WS2) via Chlorine‐Driven Chemical Vapor Transport

Abstract: Large-scale production of high-quality tungsten disulfide (WS ) monolayers is a prerequisite for potential device applications using this promising transition metal dichalcogenide semiconductor. The most researched technique is chemical vapor deposition, typically involving the reaction of sulfur vapors with tungsten oxide. Other techniques such as physical vapor deposition have been explored with some success, but low vapor pressures make growth difficult. This study demonstrates a growth process that relies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…Recently, a small amount of NaCl salt has been used as a source of chlorine to facilitate the synthesis of single‐layer transition metal dichalcogenides, due to its lower transport ability. Furthermore, the addition of NaCl played a key role in lowering the growth temperatures, as Na‐containing precursors that condensed on the substrates provided nucleation sites and reduced the energy of the reaction .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a small amount of NaCl salt has been used as a source of chlorine to facilitate the synthesis of single‐layer transition metal dichalcogenides, due to its lower transport ability. Furthermore, the addition of NaCl played a key role in lowering the growth temperatures, as Na‐containing precursors that condensed on the substrates provided nucleation sites and reduced the energy of the reaction .…”
Section: Resultsmentioning
confidence: 99%
“…They suggested that nonvolatile WS 2 reacts with NaCl to form gaseous tungsten chloride and sulfur. 48 Wang et al synthesized MoS 2 -WS 2 in-plane heterostructures by ambient pressure chemical vapor deposition. They suggested Na-containing intermediate product is formed, which reduces the reaction energy.…”
Section: Introductionmentioning
confidence: 99%
“…The use of NaCl can modify the shape and quality of TMDs, Song et al, for example, employed NaCl as a catalyst, which is effective in comparison with S organic compounds in improving the growth rate (5 min for monolayer MoS 2 ). The MoS 2 synthesized using NaCl presented a large grain size (≈50 µm) and showed conformality on a wafer scale (≈6 in.)…”
Section: Electronic Transport Devicesmentioning
confidence: 99%